Regulation of corticotropin releasing hormone receptor type 1 messenger RNA level in Y-79 retinoblastoma cells: potential implications for human stress response and immune/inflammatory reaction - N. C. Vamvakopoulos; T. O. Sioutopoulou; Z. Mamuris; P. Marcoulatos; P. C. Avgerinos (Hindawi Limited, 1996)
We report the regulation of type 1 receptor mRNA in Y-79 human retinoblastoma cells, grown in the absence or presence of pharmacological levels of phorbol esters, forskolin, glucocorticoids and their combinations. To control for inducibility and for assessing the sensitivity of the Y-79 system to glucocorticoids, corticotropin releasing hormone mRNA levels were measured in parallel. All treatments stimulated corticotropin releasing hormone receptor type 1 gene expression relative to baseline. A weak suppression of corticotropin releasing hormone mRNA level was observed during dexamethasone treatment. The cell line expressed ten-fold excess of receptor to ligand mRNA under basal conditions. The findings predict the presence of functional phorbol ester, cyclic AMP and glucocorticoid response elements in the promoter region of corticotropin releasing hormone receptor type 1 gene and support a potential role for its product during chronic stress and immune/inflammatory reaction.